The Benefit of Community and Family Support During the Perinatal Period for Latina Immigrants - Sampson, McClain; Kennedy, Priscilla (Cuadernos Fronterizos, 2024)
Latina women are at increased risk for depression and anxiety, with rates twice those of Latino men in the United States. Specifically, among immigrants, rates of depression and anxiety increase with the number of years lived in the United States. The perinatal period (during pregnancy and up to 12 months postpartum) is a time of heightened risk for depression and anxiety for Latina immigrants, with studies demonstrating prevalence rates of between 52-54%.